Nursing of a patient undergoing surgery for lumbar compression fracture (1例腰椎压缩骨折手术患者的护理体会) - QIN Jingwen (秦婧文); WANG Qiujie (王秋洁); WANG Yuanyuan (王媛媛) (中西医结合护理, 2023)
This paper summarized the nursing of a patient with lumbar compression fracture after percutaneous kyphoplasty(PKP) operation. The nursing measures included: pain management, psychological care, safety management, prevention of potential complications, implementation of individualized rapid rehabilitation plan and continuous nursing. The step-by-step rehabilitation plan of integrated traditional Chinese and western medicine was designed to relieve the pain, shorten the recovery period, and improve the rehabilitation of spinal function and quality of life after operation. (本文总结1例腰椎压缩骨折术后患者的护理经验, 包括中医护理适宜技术、疼痛管理、心理护理、并发症预防、功能锻炼、延续性护理等。通过实施循序渐进式的康复护理, 减轻患者痛苦, 缩短康复周期, 促进脊柱区功能恢复, 实现脊柱稳定性重塑, 切实提高患者生活质量。)